WORK FROM HOME PADA MASA PANDEMI COVID-19 DITINJAU DARI PERSEPSI GURU DI KABUPATEN SIKKA MAUMERE NUSA TENGGARA TIMUR - Debi Angelina Br Barus (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2020)
This study aims to determine teacher perceptions in Sikka Maumere District related to the implementation of work from home (WFH) in the Covid-19 pandemic. The sample of this study was a random sample of 180 teachers spread across Sikka Maumere Regency. This research measuring instrument using a perception questionnaire consisting of three aspects, namely cognitive, affective and conative aspects. Perception measuring instrument in this study was tested on 30 teachers with the results of the coefficient of validity (rxy) ranging from 0.417 to 0.558 with a reliability of 0.829. The results of this study indicate that from the cognitive aspect found an empirical mean of 9.18 <hypothetical mean, it is concluded that from the cognitive aspect the teacher has a negative perception of work from home. While the affective and conative aspects were found to mean 12.06 and 12.36, respectively, where the mean epirical> hypothetical mean, it was said that from the affective and conative aspects, teacher perceptions in Sikka Maumere District towards work from home during the positive co-19 pandemic. The results found 98 teachers or 54.5% had positive perceptions related to the implementation of work from home in the Covid-19 pandemic and 82 teachers had negative perceptions of work from home in the Covid-19 pandemic. Keywords: Work from home, teacher perceptions, covid-19 pandemic. Penelitian ini bertujuan untuk mengetahui persepsi guru di Kabupaten Sikka Maumere terkait penerapan work from home (WFH) dimasa pandemi Covid-19. Sampel penelitian ini dengan menggunakan sampel ancidental yaitu sebanayk 180 guru yang tersebar di Kabupaten Sikka Maumere. Alat ukur peneltian ini dengan menggunakan angket persepsi yang terdiri dari tiga aspek yaitu aspek kognitif, afektif dan konatif. Alat ukur persepsi dalam penilitian ini diuji coba kepada 30 orang Guru dengan hasil koefisien validitas (rxy) berkisar antara 0.417-0.558, dengan reliabilitas sebesar 0.829. Hasil penelitian ini menunjukan bahwa dari aspek kognitif ditemukan mean empirik sebesar 9.18 < mean hipotetik maka ndisimpulkan dari aspek kognitif guru memiliki persepsi negatif terhadap work from home. Sedangkan dari aspek afektif dan konatif ditemukan mean masing-masing sebesar 12.06 dan 12,36, dimana mean epirik > mean hipotetik maka dikatakan bahwa dari aspek afektif dan konatif, persepsi guru di Kabupaten Sikka Maumere terhadap work from home dimasa pandemi covid-19 postif. Dari hasil tersebut ditemukan sebanyak 98 guru atau sebesar 54.5% memiliki persepsi positif terkait penerapan work from home dimasa pandemi Covid-19 dan sebanyak 82 guru memiliki persepsi negatif terhadap work from home dimasa pandemi Covid-19. Kata Kunci: Work from home, persepsi guru, pandemic covid-19